Fake News and Brazilian politics – temporal investigation based on semantic annotations and graph analysis - Gomes Jr., Luiz; Frizzon, Gabriel (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2019)
The widespread use of misleading news articles has been threatening democratic processes such as elections and referendums. Understanding how fake news address social entities (e.g. personalities and institutions) and how they react to social events are important factors in the fight against the trend. This paper employs a new approach based on semantic annotations and graph analysis to study fake news articles about Brazilian politics in a two-year time span. We demonstrate how graph analysis can be used to track topic evolution and cluster related entities. A preliminary result also indicates that fake news tends to be influenced by public interest (and not the other way around).